(untitled) - Zimmerman, Scott (Indianapolis, Ind., 1996)
The "ins and outs" of planning, installing, configuring and administering a Windows NT 4.0-based intranet for an organization is the focus of this kit. The book includes detailed instructions on how to use the software on the CD to develop an intranet's content: HTML pages, CGI scripts, image maps, etc.
Keywords: Mạng nội bộ (Mạng máy tính),Intranets (Computer networks)